1987
DOI: 10.1017/s0003356100036692
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of large White and Duroc boars as terminal sires under two different feeding regimes

Abstract: Large White and Duroc semen was used to form a three-breed cross from Large White x Norwegian Landrace dams. A pair of sibs from each litter was fed ad libitum and a further pair on a time-based scale at the Meat and Livestock Commission testing station at Stirling, Scotland. A total of 241 litters was tested. At the end of testing the pigs were slaughtered and standard carcass measurements were made. One side of the carcass of each of a sample of 60 pigs was fully dissected. The Duroc progeny grew faster and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 4 publications
3
8
0
1
Order By: Relevance
“…On an ad libitum feeding regimen, however, Duroc crosses grew faster (81 g/day) than Large White crosses and this was mainly the result of a higher voluntary feed intake (190 g/day). In a more recent investigation (Simpson et al 1987), which was an extension of that of Sutherland et al (1984) to evaluate more sires, the result agreed with those of the previous study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…On an ad libitum feeding regimen, however, Duroc crosses grew faster (81 g/day) than Large White crosses and this was mainly the result of a higher voluntary feed intake (190 g/day). In a more recent investigation (Simpson et al 1987), which was an extension of that of Sutherland et al (1984) to evaluate more sires, the result agreed with those of the previous study.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies where restricted feeding was adopted, have reported a similar effect (Madsen et al 1983;Sutherland et al 1984;Sigvardsson & Andersson 1985) but in some the breed difference, as in the present analysis of farm data, was not statistically significant (McGloughlin et al 1986;Simpson et al 1987). Differences in killing-out percentage in favour )f Duroc crosses over those sired by Large White or Landrace boars have also been recorded on ad ribitumfeeding, but they have generally been smaller than obtained on restricted feeding and not statistically significant (Sutherland et al 1984;Simpsonetal.1987).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The effect of the Duroc breed has been extensively studied, in particular with regard to growth performance, carcass and meat quality for light (Simpson et al, 1987;Edwards et al, 1992;Liu et al, 1999;Blanchard et al, 1999) and heavy pig production (Fabbri and Bergonzini, 1979;Santoro et al, 1981;Geri et al, 1983;Bittante et al, 1989;Caleffi and Broccaioli, 1990;Bittante et al, 1990;Bonomi et al, 1991;Franci et al, 1994 a;Franci et al, 1994 b;Bittante et al, 1993;Sabbioni et al, 2002 a), fat composition (Franci et al, 1995;Sabbioni et al, 2002 b) and cured ham characteristics (Bittante et al, 1991;Bonomi et al, 1992;Gallo et al, 1994;Franci et al, 1996).…”
Section: Introductionmentioning
confidence: 99%